Isolation and cloning ABCG1 gene from Rasbora sarawakensis - Ting, Tai Wei (Universiti Malaysia Sarawak (UNIMAS), 2016)
ABCG gene is one of the subfamily of ATP-binding cassette (ABC) transporter superfamily. Loss of function mutation of ABCG gene can lead to various human inheritance disorders such as sitosterolemia. The aims of this research are to isolate th ABCG1 partial fragment from Rasbora sarawakensis and subsequently clone by transforming the isolated fragment of interest ligated with vector into the competent cell. Degenerate primer pair was designed by aligning five different species of freshwater fish. Various optimization such as primer concentration and DNA polymerase concentration was carried out in order to determine th optimum annealing temperature of the primers. After transformation, the bacteria colony was picked and colony PCR was carried to verify the presence of inserts which was about 800bp.